1994
DOI: 10.1046/j.1365-313x.1994.05040493.x
|View full text |Cite
|
Sign up to set email alerts
|

A cotyledon regulatory region is responsible for the different spatial expression patterns of Arabidopsis 2S albumin genes

Abstract: SummaryThe 2S albumin genes of Arabidopsis thallana are a model system to study gene expression during late embryogeneeis. The at2Sl gene has previously been shown to be expressed essentially in the embryo axis, unlike at2S2, which is expressed throughout the embryo. Hybrid promoter constructs between at2Sl and at2S2 were Introduced Into Arabidopsla end used to identify a cotyledon regulatory region necessary for 2S albumin expression in palisade paranchyma and specific epidermal cells. Other promoter sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The three B3-type regulatory proteins directly activate the target genes by binding to RY motifs present in the promoters Monke et al, 2004;Reidt et al, 2000;Reinders et al, 2002). Indeed, Seed transcriptional regulatory network 613 the RY box (CATGCA) is necessary for the correct expression of several seed-specific genes in Arabidopsis (Baumlein et al, 1986(Baumlein et al, , 1992Conceicao Ada and Krebbers, 1994;Ellerstrom et al, 1996;Stalberg et al, 1993), legumes (Bobb et al, 1997;Dickinson et al, 1988) and maize (Suzuki et al, 1997), for example. Furthermore, it has been shown that FUS3, LEC2 and ABI3 can bind an RY motif in vitro (Braybrook et al, 2006;Monke et al, 2004;Reidt et al, 2000), and that LEC2 and FUS3 bind an RY motif in a yeast one-hybrid assay (Kroj et al, 2003).…”
Section: Target Promoters and The Role Of Ry Motifsmentioning
confidence: 99%
“…The three B3-type regulatory proteins directly activate the target genes by binding to RY motifs present in the promoters Monke et al, 2004;Reidt et al, 2000;Reinders et al, 2002). Indeed, Seed transcriptional regulatory network 613 the RY box (CATGCA) is necessary for the correct expression of several seed-specific genes in Arabidopsis (Baumlein et al, 1986(Baumlein et al, , 1992Conceicao Ada and Krebbers, 1994;Ellerstrom et al, 1996;Stalberg et al, 1993), legumes (Bobb et al, 1997;Dickinson et al, 1988) and maize (Suzuki et al, 1997), for example. Furthermore, it has been shown that FUS3, LEC2 and ABI3 can bind an RY motif in vitro (Braybrook et al, 2006;Monke et al, 2004;Reidt et al, 2000), and that LEC2 and FUS3 bind an RY motif in a yeast one-hybrid assay (Kroj et al, 2003).…”
Section: Target Promoters and The Role Of Ry Motifsmentioning
confidence: 99%
“…In addition, heterodimer formation seems to protect bZIP proteins from degradation (see Supplemental Figure 3 online) and therefore provides an additional mechanism that contributes to the observed synergistic effect on transcription. Although not investigated in this study, the first possibility might also explain how diversification in target binding sites can lead to variations in the expression of different SSP genes (Conceicao Ada and Krebbers, 1994), depending on the binding properties of the heterodimers prevailing temporally and spatially in the seed. In conclusion, the concurrence of several regulatory mechanisms must be operating on the underlying bZIP network.…”
Section: Specific Heterodimerization Of Bzip53 and Group C Bzips Execmentioning
confidence: 99%
“…Moreover, the progressive derepression of these seed-specific genes during emf1 development shows that their ectopic expression does not result from the residual expression of the seed maturation program after germination. Because strong emf1-2 mutants do not have carpelloid organs at 7 DAG and none of the emf1 mutants can produce seeds, seed-specific gene expression (Gaubier et al, 1993;Conceicao Ada and Krebbers, 1994) in these mutants does not result from seed development. Unlike the emf1 mutants, the seed maturation genes did not show obvious upregulation in the emf2-1 mutants, suggesting functional differences between EMF1 and EMF2 genes in the repression of the seed maturation genes.…”
Section: The Seed Maturation Program Is Upregulated In Emf1 Mutantsmentioning
confidence: 99%